GENERAL ASPECTS STRUCTURAL APPROACH IN INVESTIGATING A ROLE OF ELITES IN THE PROCESSES OF POLITICAL SYSTEM MODERNIZATION - Хорішко, Л. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The process of global development articulates the role and significance of the political systems’modernization as a factor of structural transformations and adaptations to the challenges of theenvironment. In this context, the article paid the special attention to the actors of modernization andthe local specifics and peculiarities. The article investigates the structural approach to the study ofthe role of elites in the processes of modernization of political system. The article argues that thestructural approach oriented to the investigation of social-economic and political-culturalpreconditions, which contribute to the democratic institutes’ formation in a political system, andrules of interaction between actors within the system.